Valuable everyday encounters in early childhood education: narratives from professionals. Issue 4 (20th October 2022) - Löfgren, Håkan; Manni, Annika
ABSTRACT: This article presents professionals' narratives about valuable encounters with young children in early childhood education (ECE) settings. The study aims to provide an in-depth perspective on how professionals talk about ethics in practice, and the values addressed in the narratives. Initially, professionals in Swedish ECE settings defined their understanding of a valuable encounter with a child and then used a digital app to self-register 10 such encounters during one day. After the self-registration, we interviewed the professionals and they told us about the encounters they had experienced. We identified three themes concerning who was the focus of the encounters: the professional, the child, or both reciprocally. By using a narrative approach and Nussbaum's ethical theoretical perspective, we show how different rationales were interwoven in the stories and that situated emotions were enacted and reflected. Finally, we noticed that many valuable encounters took place in 'in-between spaces'. They were not planned for or organised, but occurred spontaneously through professionals' sensitive employment of an ethics in practice.